(3MGOi GdGQhGM Edi HdGO GdCaQGMs - (3eMeO Hf CHj HcQ Hf CjhH Hf bje GdLhRjg, GHf Gdbje, TeS GdOjf, CHh YHO Gddg, J (B751 (3g` s ((3eMehO Hf CMeO Hf eMeO GdMehi Gdajhei s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd LfGJ GdaQOhS dYHGOg GdeDefjf fRdG s
(3BNQgG (B:s
(3adG JNJU GdOYhi GdePchQI HhbJ EQGOI GdTF hgPG ceG Cfg GdCdjb HeYfi GdBjI agh GdCdjb HMGdge hGddg SHMGfg GYde BNQ GdcJGH s
(3HgG fXGe GdJYbjHIs
(3aQZ GdeDda ef JCdja YTjI YQaI SfI (B745s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B56s
Keywords: (3GdJUha hGdBOGH GdTQYjIs